Aortic Arch Surgery Under Warm Conditions (Moderate to Mild Hypothermia) - Bruno, Schachner; Thomas, Ratschiller; Peter, Benedikt; Florian, Huber; Roland, Mair; Jessica, Gottsberger; Andreas, Zierer (Archives of Clinical and Biomedical Research, 2020)
Abstract not available in the source database.